Critical Skills in Teacher Education: Perceptions of Students in the Early Childhood and Preschool Education Program at the National University, Costa Rica - Ramírez-Abrahams, Patricia (2026)
Introduction. This article analyzes critical skills in teacher education among a group of students enrolled in the Pedagogy program with an emphasis on Preschool and Early Childhood Education [PEEP-PRI] at the National University of Costa Rica. The study examines students’ perception regarding their knowledge of these skills throughout their university training trajectory. Methodology. The study surveyed 91 students from the diploma, bachelor’s, and licentiate levels of the program. Critical skills were selected based on theoretical perspectives drawn from critical literacy, understood as a form of reflective and intentional reading of educational reality. The research follows a descriptive methodology and a selective design. A questionnaire was administered in which participants were asked about 19 critical skills categorized into two areas: understanding reality, explained as the reading of texts and contexts, and argumentation grounded in a personal and professional critical stance. The analysis of the study was guided by the research objectives and by the learning outcomes established in the program’s curriculum. Results. The findings reveal differences across program levels in the development of critical skills. In addition, critical reading skills were identified as the least developed among the students. Discussion. The results highlight the need to strengthen and intentionally integrate these skills into university pedagogical mediation, based on the curricular axes established in the program’s curriculum, as a means of contributing to continuous improvement in teacher education.